Cynoacrylate surgical glue as an alternative to suturing for mesh fixation in lichtenstein hernia repair - Jaiswal, Deepak; Wilkinson, TRV; Akhtar, Murtaza (International Surgery Journal, 2018)
Background: Tension free repair using mesh in open hernia repair has become more popular in recent years. Chronic pain remains a frequent complication after Lichtenstein inguinal hernia repair. The use of sutures to fix the mesh has been implicated. Fixing the mesh using cynoacrylate glue could avoid this complication. The purpose of the present study is to study the incidence of pain and other complications following inguinal hernia repair performed by the Lichtenstein technique with mesh fixation by cyanoacrylate surgical glue. Methods: T This study was conducted at tertiary care hospital. Inclusion criteria were all patients coming to the hospital with inguinal or inguinoscrotal hernias diagnosed clinically. Exclusion criteria were all complicated inguinal hernia namely obstructed, strangulated, and large hernias with scrotal abdomen, recurrent hernia. Patient not fit for surgery or not consenting to join the study. The patients will be informed about the surgery and thereafter requested to sign an informed consent. Primary outcome was postoperative pain. Secondary endpoints were operating time, surgical site infection and recurrence rate. Results: Total number of 31 cases enrolled in the study of which twenty-two had unilateral and seven had bilateral inguinal hernias. Average pain score on POD 1, 3, 7 was 5.75; 4.53; 3.32 respectively. One patient developed seroma which was managed conservatively. No evidence of recurrence during study period. Conclusions: Cyanoacrylate surgical glue is a reliable method and can be used as an alternative for conventional Lichtenstein hernia repair.